STUDI LITERATUR: FAKTOR FENOMENA THEORY JUMPING DALAM PEMBANGUNAN NEGARA BERKEMBANG: ANTARA ADAPTASI DAN KETERGANTUNGAN - Muhammad Alfi Naufal Nizar (LPPM UNSAP, 2026)
The development of development theory shows a paradigm shift from a linear approach to a more adaptive and innovative approach. One of the new paradigms thathas emerged is Jumping Theory or Leapfrogging Development, which emphasizes the ability of developing countries to leapfrog conventional stages of development using innovation, technology, and institutional reform. This paper aims to examine the concept of Jumping Theory in the context of development theoryand issues, with reference to the views of Lee (2019) and Burlamaqui and Kattel (2016). Through a conceptual approach, the discussion focuses on the main characteristics of this theory, its relevance to the Indonesian context, and its comparison with classical development theories such as linear theory, dependency theory, and endogenous development theory. The results of the discussion show that Jumping Theory offers an alternative framework that emphasizes the importance of innovation, policy flexibility, and accelerated adaptation to global changes. In the Indonesian context, this theory is relevant for understandingdevelopment strategies based on digitalization, the green economy, and bureaucratic reforms oriented towards efficiency and innovation